Analisis Minat Dalam Bermain Sepakbola Siswa SD Inpres Sarroanging Kecamatan Bungaya Kabupaten Gowa - Andi Rizal; Arwan; Syahrul Saleh (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
This research aims to obtain answers to the t problem. This research is a type of quantitative descriptive research that is categorical on the overall population of male students at SD Inpres Sarroanging Gowa, using 61 random male students as respondents. The instrument for collecting data is a closed questionnaire whose validation and reliability have been tested (Sujana, 2001). Next, data analysis uses percentage descriptive techniques. From statistical calculations it is known that: There are 10 students (19.6%) in the